Evaporação da água do solo sob diferentes taxas de cobertura com resíduos vegetais - Gava, Ricardo (2010)
This study was conducted at the Agronomic Institute of Paraná (IAPAR) in Londrina, Paraná (latitude 23º18'S, longitude 51º09'O and an average altitude of 585 m). The climate of Londrina, according to the classification of Köppen, is type Cfa ie humid subtropical climate, with rainfall in all seasons and can occur in the dry winter season. Determined the soil water evaporation (E) under different rates of coverage with plant residues. Treatments were installed in the weighing lysimeters of 2.66 m2 and 1.3 m deep, which determine E by difference in mass precisely equal to 0.1 mm in one hour intervals. The observed periods were approximately 30 days, two periods with different rates and two periods with different fractions of coverage. And to determine coverage rates under different, we used 0, 2.5, 5 and 10 t ha-1 of dry wheat, placed evenly in each lysimeter. And with already to determine the different fractions of coverage, it has been the amount equivalent to 5 t ha-1 of dry wheat, distributing it in, 25, 50, 75 and 100% soil cover. We conducted a test of retention of water by straw, in the Laboratory of Agricultural Engineering of IAPAR to determine the maximum amount of water retained by the straw of wheat, weighing three samples of straw collected at random in a field of wheat in three humidity conditions: sun-dried, moistened with water and dried in an oven. With different rates, from September 22 to October 20, 2008 (PT1), the reduction of E with respect to bare soil was 4, 15 and 24%, while in period 1 to December 30, 2008 (PT2), the reduction was 15, 22 and 25% respectively for the treatments of 2.5, 5 and 10 t ha-1. With different fractions of coverage, from October 28 to November 27, 2008 (PF1) the reduction of E was about 11, 17, 27 and 26% compared to bare soil, while the period of 19 January to February 16, 2009 (PF2) reduction was 22, 37, 45 and 56% respectively, for treatments 25, 50, 75 and 100% soil cover. Straw sun-dried moisture was approximately 14% and reached 168% after wetting.